Oedometric study of dredged marine soils admixed with sand for settlement reduction - S.M Johan, Siti Farhanah; Chan, Chee Ming (2017)
Dredged marine soils (DMS) can be reused as fill materials for land reclamation project other than dump back to the open sea. However, in Malaysia, dredged marine soils were considered as a geowaste because of it has poor engineering properties. In the present study, dredged marine soils were excavated from the dredging works near the jetty of Kuala Perlis, Malaysia. To investigate the settlement reduction of DMS, a sand-mixed was used in this study and these results were compared with natural DMS (without sand). Oedometer test were conducted to calculate the consolidation properties of DMS and k-value can be obtained from the test. The test results showed that the dissipation of water from soils occurs faster in the sand-mixed compare to the control sample (without sand) due to the drainage path that have been reduced (two-way drainage).